Tata Kelola Pusat Kuliner Pantai Padang: Studi atas Peran Pemerintah dalam Penataan Fasilitas Publik - Arabbi, Muhammad Thufeil; Yuliarti, Yuliarti (YASIN, 2025)
This study is motivated by the suboptimal utilization of culinary areas following the relocation of street vendors (PKL), limited public facilities, and weak enforcement of existing policies. The aim of this research is to analyze the governance of the Pantai Padang Culinary Center by the Padang City Tourism Office in supporting the availability of proper public facilities for both residents and visitors. A descriptive qualitative approach was employed, involving nine informants representing government officials, vendors, and visitors. Data were collected through interviews, observation, and documentation, and analyzed using the interactive model by Miles and Huberman, which includes data reduction, data presentation, and conclusion drawing. The findings indicate that while the area’s governance has shown adequate planning supported by regulations and the provision of basic facilities, the organizational process remains suboptimal, and supervision is limited to administrative procedures without a continuous monitoring system. Supporting factors include government policy, initial facility provision, and entrepreneurship training. However, challenges persist, such as vendor resistance, limited supporting infrastructure, and weak field supervision. The study concludes that the governance of the Pantai Padang Culinary Center is not yet fully effective and requires strengthening in implementation and oversight. These findings are expected to serve as a foundation for formulating participatory, adaptive, and sustainable policies for culinary area management. Keywords: Governance; Culinary Center; Public Facilities; Street Vendor Relocation; Padang City Tourism